2018
DOI: 10.1016/j.ijheatfluidflow.2018.04.010
|View full text |Cite
|
Sign up to set email alerts
|

The development and application of two-time-scale turbulence models for non-equilibrium flows

Abstract: This study re-visits the largely overlooked, but highly promising, topic of multi-scale RANS modelling for non-equilibrium turbulent flows. The paper presents the development of RANS models which, at an effective-viscosity level, involve two transport equations for the turbulent kinetic energy; one for the energy of the large scale, energy-producing, eddies and one for that of the smaller eddies, which, through continuous break-up, transfer turbulence energy to the dissipative scales. Two transport equations f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…Turbulence models with multiple time scales have been treated in (Hanjalić et al, 1980), with more recent further development to be found in (Klein et al, 2018). We base our discussion on homogeneous flow, where equations for the time evolution of 𝑘 and 𝜀 can be written (Hamlington & Ihme, 2014):…”
Section: 𝑘 − 𝜀 Turbulence Model With Two Time Scalesmentioning
confidence: 99%
“…Turbulence models with multiple time scales have been treated in (Hanjalić et al, 1980), with more recent further development to be found in (Klein et al, 2018). We base our discussion on homogeneous flow, where equations for the time evolution of 𝑘 and 𝜀 can be written (Hamlington & Ihme, 2014):…”
Section: 𝑘 − 𝜀 Turbulence Model With Two Time Scalesmentioning
confidence: 99%
“…Turbulence models with multiple time scales have been treated in [27], with more recent further development to be found in [28]. We base our discussion on homogeneous flow, where equations for the time evolution of k and ε can be written as [29]:…”
Section: K − ε Turbulence Model With Two Time Scalesmentioning
confidence: 99%
“…There are quite a number of turbulence models within the eddy-viscosity framework. Recent advances on the numerical modelling of turbulent flows can be found in the papers by Argyropoulos and Markatos [1], Klein et al [2,3], and Nie et al [4]. Despite its many shortcomings, the k-ε model of turbulence is one of the most widely used turbulence models and it is capable of simulating an extensive collection of flows.…”
Section: Introductionmentioning
confidence: 99%